1998
DOI: 10.1677/joe.0.1570267
|View full text |Cite
|
Sign up to set email alerts
|

Rab3B is essential for GnRH-induced gonadotrophin release from anterior pituitary cells

Abstract: Gonadotrophin-releasing hormone (GnRH) induces the release of gonadotrophins via an increase in cytosolic Ca 2+ concentration ([Ca 2+ ]). Rab3B, a member of the small GTP-binding protein Rab family, is known to be involved in Ca 2+ -regulated exocytosis in pituitary cells. However, it is not known whether Rab3B functions in the physiological process regulated by GnRH in gonadotrophs. In this study using antisense oligonucleotide against Rab3B (AS-Rab3B) we determined that Rab3B is involved in GnRH-induced gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…The more conspicuous GTPases found in secretory granules with a function in exocytosis are Rab3 isoforms, but most studies report an inhibitory role for these proteins (12). However, a stimulatory role has been suggested in some secretory events (14)(15)(16). In this report we show that Rab3A is essential for the calcium-dependent acrosome reaction.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The more conspicuous GTPases found in secretory granules with a function in exocytosis are Rab3 isoforms, but most studies report an inhibitory role for these proteins (12). However, a stimulatory role has been suggested in some secretory events (14)(15)(16). In this report we show that Rab3A is essential for the calcium-dependent acrosome reaction.…”
Section: Discussionmentioning
confidence: 55%
“…Rab3A is one of the best-characterized Rabs, whose three-dimensional crystal structure in association with a putative effector has been solved at 2.6-A resolution (13). Curiously, Rab3 isoforms seem to be negative regulators in several exocytotic events (12), although an activating role also has been proposed in other exocytotic models (14)(15)(16).…”
mentioning
confidence: 99%
“…In a previous report by Tahara et al (1999), the expression of rab3 in human pituitary adenomas was found by immunohistochemical staining. Another report by Tasaka et al suggested that rab3B was indispensable for GnRH-induced gonadotropin release (Tasaka et al, 1998). However, the direct function of rab3B in conjunction with the secretion of pituitary hormones is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous reports have either mainly studied rab family, or have focused exclusively on the SNARE system (Jacobsson and Meister, 1996;Lledo et al, 1993;Quintanar and Salinas, 2002;Salinas et al 1999;Tahara et al, 1999;Tasaka et al, 1998), to date these proteins have not yet been investigated together. Therefore, their mutual relationships have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that rab3B is a key intracellular signaling molecule that can control exocytosis in anterior pituitary cells [16]. Tasaka et al suggested that rab3B is indispensable for gonadotropinreleasing hormone (GnRH)-induced gonadotropin release [39]. They reported that rab3B is involved in basal and GnRH-induced gonadotropin release but not gonadotropin storage, and that rab3B is essential for GnRH-regulated exocytosis downstream of cytosolic Ca 2+ in gonadotrophs.…”
Section: Functional Analyses Of Rab3b In Pituitary Cellsmentioning
confidence: 99%